2016
DOI: 10.21608/bvmj.2016.31281
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins residues in chicken and turkey tissues

Abstract: Total aflatoxins residues were detected in chicken and turkey tissues "muscles and liver " by using HPLC. Results revealed a significant difference variation among liver and muscles in examined chicken and turkey's samples (p values <0.05). These indicated that liver is the reservoir place of total aflatoxins residues. The means average of Aflatoxin B1, G1, B2, G2 and total aflatoxins residues respectively, in examined chicken liver samples were 17.3+/-3.3 µg/kg, 13.5+/-2.1µg/kg, 7.6+/-4.8 µg/kg ,1.5+/-0.9 µg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The obtained results were agreed with those achieved by Resanović, 2000 andSaeed et al, 2003 who declared that however aflatoxins residues found in liver, muscles, stomach, kidneys, adipose tissue and meat but liver is the harbor site of aflatoxin residues. In the same line the results agreed with those obtained by Bennett and Klich, 2003, Miliţăet al, 2010, Herzallah, 2013, Hasanen et al, 2016and Darwish et al, 2016 who reported that the highest concentration of AFB1 and total aflatoxins were in liver higher than in kidneys than in gizzard, while the lowest concentrations were in thigh and breast. The present results are completely disagreed with those achieved by Abo El-Yazeedetal., 2015 who detected that the residual concentrations were higher in breast than in liver.…”
Section: Discussion Mycotoxins Residues In Different Chicken Productssupporting
confidence: 89%
“…The obtained results were agreed with those achieved by Resanović, 2000 andSaeed et al, 2003 who declared that however aflatoxins residues found in liver, muscles, stomach, kidneys, adipose tissue and meat but liver is the harbor site of aflatoxin residues. In the same line the results agreed with those obtained by Bennett and Klich, 2003, Miliţăet al, 2010, Herzallah, 2013, Hasanen et al, 2016and Darwish et al, 2016 who reported that the highest concentration of AFB1 and total aflatoxins were in liver higher than in kidneys than in gizzard, while the lowest concentrations were in thigh and breast. The present results are completely disagreed with those achieved by Abo El-Yazeedetal., 2015 who detected that the residual concentrations were higher in breast than in liver.…”
Section: Discussion Mycotoxins Residues In Different Chicken Productssupporting
confidence: 89%
“…The results of the total mycotoxins in local and imported livers chicken samples in (Table, 2) showed significant differences at (P≤0.05) among them, the levels of mycotoxins AFB1 increased in the livers of Brazilian chicken, as it reached 1.73 µg/g, the Turkish 1.53 µg/g and the local 1.35 µg/g. .42 and 92.15)%, respectively, and its concentration exceeded 10 μg/kg in all samples, which is the maximum allowable level in animal foods, (Hasanen et al, 2016) when studying the accumulation of mycotoxins in the tissues and organs of Egyptian chickens, indicated that the liver is a home for the remains of these toxins, especially AFB1, despite its presence in the muscles, stomach, kidneys, and fatty tissues. (6.1, 13, and 2.2) µg/g respectively, for AFB1, AFB2, AFG1, AFG2, Darwish et al, (2016) also confirmed in his study in Egypt that the total concentration of aflatoxin was in the liver 3.4 µg/g, which is higher in the kidneys compared to gizzards, while the lowest concentrations were in breast and thigh meat at a concentration of 0.5 µg/g, (El-Tawaab et al, 2019) stated that the liver and kidneys of poultry containing mycotoxins intended for human consumption should not be allowed to be consumed, they also indicated that feeding poultry on feed contaminated with mycotoxins is the reason for the high concentrations of toxins in these organs, poor refrigeration is another cause of mold contamination, whereby food spoilage occurs, which promotes the production and increase of mycotoxins such as aflatoxin.…”
Section: Mycotoxinsmentioning
confidence: 84%
“…Inadequate storage and/or warehousing conditions lead to aflatoxin biosynthesis [15]. AFB1 contamination of poultry feed available in Dakar region raises thorny issues of animals and consumers health through food chain (residues in chicken tissues and eggs) [33] R. Means with different letters in same row are significantly different.…”
Section: Resultsmentioning
confidence: 99%